P14 Testing for pharyngeal gonorrhoea in women: an important reservoir of infection, or excessive false positive diagnoses. (18th May 2015) - Forbes, Georgina; Drayton, Rachel
Abstract : Background: In 2012 we reported that 30% of heterosexual women attending our service had a positive gonorrhoea (GC) NAAT on pharyngeal sampling, without infection elsewhere. A PPV of 87% has been reported for our pharyngeal samples, but confirmatory GC NAATs remain routinely not available locally. Due to concerns about false positives, we subsequently restricted pharyngeal testing to women at higher risk of infection at this site only and reviewed the findings. Methods: All positive GC NAATs in women attending our service from October 2013 to March 2014 were reviewed. Findings were compared to the data from January to July 2012. All NAATs were performed on Roche Cobas 4800. Results: There were 36 women in the 2014 sample, compared to 40 in the 2012 sample. Of these, 19 (53%) had a positive GC NAAT on a pharyngeal sample, compared to 17 (43%) in the 2012 sample (p = 0.38). 13 (36%) of women with a positive GC NAAT had the infection detected on pharyngeal swab only in the 2014 sample, compared to 12 (30%) in the 2012 sample (p = 0.56). Discussion: By restricting testing to women at higher risk of pharyngeal only infection, we found 36% women had an isolated positive pharyngeal GC NAAT, and would not have been diagnosed if pharyngeal sampling was not taken. Further work is needed assessing the performance of the Roche Cobas 4800 in this population in order to evaluate the proportion of false positive diagnoses versus the extent of this potential reservoir of infection.